THE APPLICATION OF TEAMS GAME TOURNAMENT (TGT) MODEL WITH AUDIO VISUAL MEDIA IN IMPROVING SOCIAL STUDIES OF THE FIFTH GRADE STUDENTS OF SDN 4 KUTOSARI IN ACADEMIC YEAR 2014/2015 - Ayusari, Desy Dwi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Teams Game Tournament (TGT) Model with Audio Visual Media in Improving Social Studies of The Fifth Grade Students of SDN 4 Kutosari In Academic Year 2014/2015. The objectives of the research are: to improve social studies. This research is a collaborative Classroom Action Research (CAR) that was conducted in three cycles. This research use four steps, there are planning, actuating, observation, and reflection. Subject of the research are fifth grade students of SDN 4 Kutosari in academic year of 2014/2015, totalling 40 students. Validity of data uses triangulation technique in the form of triangulation of data sources and data collecting technique. The sources of data in this research were students, fifth grade teacher, document, and peers. Techniques of collecting data are test and non test. The results show that the application of Teams Game Tournament (TGT) model with audio visual media can improve social studies with KKM ? 70 in the first cycle was 33,75%, 57,5% in the second cycle and 85% in the third cycle. Keywords: Teams Game Tournament (TGT), audio visual, social studies Abstrak: Penerapan Model Pembelajaran Kooperatif Tipe Teams Game Tournament (TGT) Disertai Media Audio Visual untuk Meningkatkan Pembelajaran IPS pada Siswa Kelas V SD Negeri 4 Kutosari. Tujuan penelitian yaitu: untuk meningkatan pembelajaran IPS siswa. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaboratif dilaksanakan dalam tiga siklus. Penelitian ini menggunakan empat tahapan, yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian adalah siswa kelas V SDN 4 Kutosari tahun ajaran 2014/2015, berjumlah 40 siswa. Validitas data menggunakan teknik triangulasi yang berupa triangulasi sumber data dan teknik pengumpulan data. Sumber data dalam penelitian ini yaitu siswa, guru kelas V, dokumen, dan teman sejawat. Teknik pengumpulan data yang digunakan yaitu tes dan non tes. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe Teams Game Tournament (TGT) disertai media audio visual dapat meningkatkan pembelajaran IPS dengan KKM ? 70 pada siklus I sebesar 33,75%, siklus II 57,5%, dan siklus III 85%. Kata kunci: Teams Game Tournament (TGT), audio visual, pembelajaran IPS